Eficacia del Mindfulness como tratamiento para el insomnio en adultos. - Falcón Lema, Claudia Elizabeth (2024)
This research aims to focus on analyzing the efficacy of Mindfulness as a treatment for insomnia in adults, taking into account a population of patients who have been diagnosed with cancer. This research was a bibliographic and descriptive review. The population is composed of 280 documents published in the last 10 years, in English and Spanish, while the sample is composed of 42 scientific articles. These documents were collected from databases such as Scopus, Pubmed, Google Scholar, Wiley Online Library, Springer Link, and Scielo. Bibliographic review techniques and a methodological quality review were used, as well as instruments such as a review form, a document matrix, and the CRF-QS matrix. Among the results, it was identified that Mindfulness interventions on insomnia in patients detected with cancer generated positive effects leading to a reduction in the severity of insomnia and a better quality of sleep, in addition to evidencing a decrease in anxiety, depression, fatigue, perceived stress, pain, among others, leading to a better quality of life. Finally, it was determined that most of the Mindfulness interventions were effective in the treatment of insomnia. In conclusion, the application of Mindfulness-based interventions in general has shown favorable results, mainly MBSR and MBCR, reflecting in patients diagnosed with cancer an improvement in their sleep quality, thus decreasing the level of insomnia.